Genome-Wide Identification of Powdery Mildew Responsive Long Non-Coding RNAs in Cucurbita pepo - Tian, Jiaxing; Zhang, Guoyu; Zhang, Fan; Ma, Jian; Wen, Changlong; Li, Haizhen (Frontiers in Genetics, 2022)
Cucurbita pepo L. is an essential economic vegetable crop worldwide, and its production is severely affected by powdery mildew (PM). However, our understanding of the molecular mechanism of PM resistance in C. pepo is very limited. Long non-coding RNAs (lncRNAs) play an important role in regulating plant responses to biotic stress. Here, we systematically identified 2,363 reliably expressed lncRNAs from the leaves of PM-susceptible (PS) and PM-resistant (PR) C. pepo. The C. pepo lncRNAs are shorter in length and expressed at a lower level than the protein-coding transcripts. Among the 2,363 lncRNAs, a total of 113 and 146 PM-responsive lncRNAs were identified in PS and PR, respectively. Six PM-responsive lncRNAs were predicted as potential precursors of microRNAs (miRNAs). In addition, 58 PM-responsive lncRNAs were predicted as targets of miRNAs and one PM-responsive lncRNA was predicted as an endogenous target mimic (eTM). Furthermore, a total of 5,200 potential cis target genes and 5,625 potential trans target genes were predicted for PM-responsive lncRNAs. Functional enrichment analysis showed that these potential target genes are involved in different biological processes, such as the plant-pathogen interaction pathway, MAPK signaling pathway, and plant hormone signal transduction pathway. Taken together, this study provides a comprehensive view of C. pepo lncRNAs and explores the putative functions of PM-responsive lncRNAs, thus laying the foundation for further study of the regulatory mechanisms of lncRNAs responding to PM.